Genetic diversity of Azotobacter strains isolated from soils by amplified ribosomal DNA restriction analysis - Mazinani, Z.; Asgharzadeh, A. (Цитология и генетика, 2014)
Strains of Azotobacter mediate in the nitrogen fixation process by reducing of N2 to ammonia. In this study, 50 strains were isolated from different rhizospheric soil in central Iran, by using soil paste-plate method. These strains were biochemically identified and characterized on differential LG medium based on morphological and physiological properties. Results obtained showed that identified strains were belonging to three species, namely A. chroococcum, A. vinelandii and A. beijernckii. In order to molecular analysis, the 16S rRNA gene was amplified using 27f and 1495r primers and PCR products were subsequently restricted with RsaI, HpaII and HhaI. Cluster analysis based on amplified ribosomal DNA restriction analysis were revealed intraspecific polymorphism and differentiated strains into two mains clusters, clusters A and B. Cluster A strains were related to the A. vinelandii, whereas cluster B strains were related to the A. chroococcum and A. beijerinckii. The results show that amplified ribosomal DNA restriction analysis is a powerful and discriminatory tool for the identification of members of the genus Azotobacter. Штаммы Azotobacter являются посредниками в проессах фиксации азота, восстанавливая N2 до аммония. Из разных ризосферных почв Ирана выделено 50 штаммов. Эти штаммы биохимически идентифицированы и охарактеризованы на дифференциальной среде LG на основе морфологических и физиологических свойств. Полученные результаты показали, что идентифицированные штаммы принадлежат трем видам – A. chroococcum, A. vinelandii и A. beijerinckii. Для молекулярного анализа ген 16S рРНК был амплифицирован с использованием 27f и 1495r праймеров, а продукты ПЦР расщеплены с помощью RsaI, HpaII и HhaI. Кластерный анализ, основанный на рестрикционном анализе амплифицированных рибосомальных ДНК (ARDRA), показал межвидовой полиморфизм и разделение штаммов на два основных кластера, A и B. Линии кластера А относятся к A. vinelandii, а кластера В – к A. chroococcum и A. beijerinckii. Результаты показывают, что ARDRA является эффективным методом идентификации видов рода Azotobacter. We would like to express our special gratitude to Dr. M. Khosroshahli (Department of biotechnology) for his helpful support. This work was supported by Islamic Azad University, Science and Research Branch, Tehran, Iran.